Mutational profiling of Chinese patients with thyroid cancer - Du, Yaying; Zhang, Shu; Zhang, Gang; Hu, Jiaying; Zhao, Lianhua; Xiong, Yuanyuan; Shen, Lu; Chen, Rongrong; Ye, Ke; Xu, Yan (Frontiers in Endocrinology, 2023)
Background: The incidence of thyroid cancer in China has rapidly increased in recent decades. As the genetic profiles of thyroid cancer vary dramatically between different geographical regions, a comprehensive genetic landscape of thyroid cancer in the Chinese population is urgently needed. Methods: We retrospectively included thyroid cancer patients from three Chinese medical centers between February 2015 and August 2020. To dissect the genomic profiling of these patients, we performed targeted next-generation sequencing on their tumor tissues using a 1,021-gene panel. Results: A total of 458 Chinese patients with thyroid cancer were enrolled, including four malignant histological subtypes arising from follicular epithelial thyroid cells. BRAF driver mutations were identified in 76.0% of patients, followed by RET rearrangements (6.8%) and RAS driver mutations (4.1%). Tumors with more somatic mutations correlated with worse clinical characteristics, including older age at diagnosis, less differentiation of tumor, larger tumor size, lymph node metastasis and distal metastasis. Subclonal BRAF mutations occurred in 20% (6/30) of patients and were frequent in poorly differentiated or anaplastic tumors (33.3% [2/6] vs. 4.2% [1/24], P = 0.09) and those with distal metastasis (50.0% [2/4] vs. 8.7% [2/23], P = 0.09). Tumors with TERT promoter mutations had significantly more somatic mutations (average: 6.5 vs. 1.8, P < 0.001). Moreover, TERT promoter mutations were not associated with lymph node metastasis but significantly associated with older age at diagnosis and poorly differentiated or anaplastic tumors, regardless of their clonal architecture. Conclusions: Our results shed light on the molecular pathogenesis and clinical characteristics of thyroid cancer in the Chinese population. The number of somatic mutations, TERT promoter mutations, and the clonal architecture of BRAF mutations should be considered in the risk stratification of thyroid cancer.